Correlation Study of Environmental Knowledge, Attitudes, Subjective Norms and Perceptions of Behavior Control on Students' Environmental Care Behavior - Agus Siswono; Lailan Syaufina; Siti Badriyah Rushayati (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to examine the correlation of environmental knowledge, attitudes, subjective norms, and perceptions of behavioral control on the environmental behavior of students of SMK-SMAK Bogor, to examine differences in environmental knowledge and environmental behavior of male students and female students of SMK-SMAK Bogor. The sample in this study was 54 students. Correlation analysis was performed using Partial Least Square (PLS). The t-test analysis was used to examine differences in knowledge and the environmental behavior of male and female students. Based on the analysis, it is known that knowledge has a positive and significant effect on attitudes; attitudes have a significant effect on environmental behavior. Meanwhile, subjective norms and perceived behavioral control have no significant effect on the environmental behavior of students at SMK-SMAK Bogor. The results of the t-test analysis also showed that the knowledge and environmental behavior between male students and female students were not significantly different.